Enhancing the productivity of irrigated Bt cotton (Gossypium hirsutum) by transplanting technique and planting geometry - SALAKINKOP, S R (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2007–09 in Upper Krishna Project command area at Agricultural Research Station, Bheemarayanagudi, Karnataka to study the comparative performance of Bt-cotton (Gossypium hirsutum L.) under in transplanting and dibbling methods at different planting geometry. Significantly higher seed cotton yield was obtained from the transplanting of seedlings (3.86 to 4.26 tonnes/ha) than the farmers’ practice of dibbling (3.27 tonnes/ ha).Transplanting increased the cotton yield by 17 to 25% and net returns by 12 to 32% compared to dibbling. Potential yield of Bt cotton both under normal and delayed sowing conditions could be enhanced by transplanting which resulted in better establishment, early vigour, early flowering and increased yield attributes. Leaf reddening in transplanted Bt cotton was reduced (7.8 to 9.2%) compared to dibbled cotton (19%). Among the transplanting geometry, spacing of 90cm×90cm recorded the highest seed cotton yield and it was at par with spacing’s of 120cm×90cm and 120cm×60cm.Yield attributes, like sympodial branches, bolls/plant, and boll weight were significantly higher in different transplanting geometry than in farmer’s practice of hand dibbling. Transplanting at 90cm×90cm, 120cm×90cm and 120cm×60cm geometries were at par with each other in respect of yield components and yield, but superior over the other transplanting spacings and hand dibbling practice.